SCHOOL INCLUSION OF DEAR: A BIOSOCIAL APPROACH - Edimario dos Santos Souza, José; da Silva, Alex; Tacyelle Santos Gomes, Heloísa; Farias Santos da Silva, Adriana; Maria da Silva, Aurineia; Paula Alves Pereira, Débora; dos Santos Lins, Givaldo; Afonso Alves Geronimo, Manuel; Santos Costa, Roseane; Januária da Silva Araujo, Silvia (Revista Gênero e Interdisciplinaridade, 2024)
This article addresses the school inclusion of deaf people from a biosocial perspective, a topic of great relevance in the context of inclusive education. Recognizing the importance of addressing this issue in depth, the study proposes a detailed analysis of deaf education, encompassing historical, cultural and pedagogical aspects. The justification for developing this research lies in the growing need to guarantee an educational environment that promotes the learning and integral development of deaf students, respecting their specificities and rights. The objectives of the study include understanding the biological and social factors that influence the school inclusion of deaf people, analyzing effective pedagogical strategies for this audience and promoting critical reflection on the inclusive process in schools. The methodology adopted involves a comprehensive literature review, complemented by case studies that illustrate successful educational practices. The main results indicate that the school inclusion of deaf people still faces significant challenges, such as the lack of preparation of education professionals and the lack of adequate resources. However, there is also progress in public policies and awareness about the importance of teaching adapted to the needs of the deaf. The discussion reveals that inclusion goes beyond the simple physical insertion of the student in the classroom, requiring structural and attitudinal changes in the school and in society.